Technological innovation and its influence on the economic development of the Ecuador period 2012-2017. - Curiel, Ángel (SATHIRI, 2020)
Recently, Ecuador has shown low productivity; for this reason it was necessary to do an exhaustive analyzes about technogogical innovation and its influence in the economical development. For this researching it was important to get information of National and International Organizations that are in relationship with Reasearching, Development and Innovation. The collection andanalyzes of data was executed with technological programs such as: EXCEL and SPSS. This information was proved through hypothesis, using the statistical pattern “chi-cuadrado” (X^2).This kind of results compares the verified ditribution with the planned distribution. So, it has been possible to get reliable results. These results are based on the differences that get the probability distribution to contrast. With this kind of analyzes it was proved that technological innovation not contributed meaningfully in the economical developement. Furthermore, proposal has beben submitted of public politics and technological innovation to help the productivity and to get an excellent knowledge based on the intellect and be possible to believe, value and share to be used in an efficient way.